Noninvasive neuromonitoring: current utility in subarachnoid hemorrhage, traumatic brain injury, and stroke - Vinciguerra, Luisa; Bösel, Julian (Neurocritical care, 2017)
Noninvasive neuromonitoring is increasingly being used to monitor the course of primary brain injury and limit secondary brain damage of patients in the neurocritical care unit. Proposed advantages over invasive neuromonitoring methods include a lower risk of infection and bleeding, no need for surgical installation, mobility and portability of some devices, and safety. The question, however, is whether noninvasive neuromonitoring is practical and trustworthy enough already. We searched the recent literature and reviewed English-language studies on noninvasive neuromonitoring in subarachnoid hemorrhage, traumatic brain injury, and ischemic and hemorrhagic stroke between the years 2010 and 2015. We found 88 studies that were eligible for review including the methods transcranial ultrasound, electroencephalography, evoked potentials, near-infrared spectroscopy, bispectral index, and pupillometry. Noninvasive neuromonitoring cannot yet completely replace invasive methods in most situations, but has great potential being complementarily integrated into multimodality monitoring, for guiding management, and for limiting the use of invasive devices and in-hospital transports for imaging.